The influence of biostimulations on the yield and quality of Brassica oleracea hybrids in the Non-Chernozem zone of the Russian Federation - A. E. Markarova; M. Yu. Markarova; S. M. Nadezhkin (Овощи России, 2024)
Relevance. It is necessary to search for methods for obtaining environmentally friendly products and reducing the pesticide load on agrobiocenoses. Biostimulants can influence the increase in the yield of vegetable crops and improve their quality, which is confirmed by numerous studies. Stimulating effects depend on a combination of various biotic and abiotic factors. The aim of the study was to assess the effect of biostimulants on the yield and quality of Brassica Oleracea in the conditions of the Central Non-Chernozem zone on heavy loamy sod-podzolic soils.Methodology. A field experiment was carried out in the conditions of the Non-Chernozem zone of the Russian Federation on sod-podzolic soil in 2019-2021. In an experiment with two hybrids of Brassica Oleracea: F1 Zarnitsa (mid-early) and F1 Mechta (late-ripening), biostimulants Agrofil and MBK-BIS were studied for soaking seeds, seedlings and foliar treatment. The control variants were without fertilizer (absolute control) and the N90P120K150 background.Results. The effect of mineral fertilizers on both hybrids was characterized by an increase in the weight of heads of cabbage by 11.7 and 23.5%, respectively. When treating seeds, the weight of heads of cabbage increased by 15-18% compared to the background. Additional treatment with stimulants for soaking seedlings in Agrofil and foliar treatment with the MBK-BIS preparation increased the weight of heads of cabbage in comparison with the background in the F1 Zarnitsa hybrid by 21.4 and 23.3%, F1 Mechta - by 21.4 and 25.4%. The contribution of biostimulants to the yield of the used cabbage hybrids is more pronounced in the late-ripening hybrid, which directly depends on the amount of precipitation during the growing season. The studied biostimulants contribute to an increase in the content of vitamin C, fiber, and the amount of sugars in cabbage heads.Conclusion. Biostimulants MBK-BIS and Agrofil are effective for increasing the yield and improving the biochemical composition of the studied Brassica oleracea hybrids in the conditions of the Non-Chernozem zone of Russia.